ASSESSING SEWER–GROUNDWATER INTERACTION AT THE CITY SCALE BASED ON INDIVIDUAL SEWER DEFECTS AND MARKER SPECIES DISTRIBUTIONS - Wolf L.; Eiswirth M.; Hötzl H. (My University, 2006)
By combining a sewer defect database and hydrogeological information, it has been attempted to assess sewer–groundwater interaction at the scale of the city of Rastatt (SW-Germany). Comprehensive hydrochemical samplings, including a series of new marker species, have been conducted in the urban aquifer and used for validation. The iodated X-ray contrast media, amidotrizoic acid and iothalamic acid, can be considered as highly specific for wastewater influence and have been found in several groundwater observation wells.
Keywords: URBAN GROUNDWATER; SEWER SYSTEM; SEWER DEFECTS; MARKER SPECIES